Local and global asymptotic behavior of malaria-filariasis coinfections in compliant and noncompliant susceptible pregnant women to antenatal medical program in the tropics - Oluwatayo M. Ogunmiloro (E-Journal of Analysis and Applied Mathematics)
In this paper, a mathematical nonlinear model system of equations describing the dynamics of the co-interaction between malaria and filariasis epidemic affecting the susceptible host population of pregnant women in the tropics is formulated. The basic reproduction number ${R_{mf}}$ of the coepidemic model is obtained, and we investigated that it is the threshold parameter between the extinction and persistence of the coepidemic disease. If ${R_{mf} < 1}$, then the disease-free steady state is both locally and globally asymptotically stable resulting in the disease dying out of the host. Also, if ${R_{mf} > 1}$, the disease lingers on. The center manifold theory is used to show that the unique endemic equilibrium is locally asymptotically stable. However, variations in the parameter values involved in the model build up will bring about appropriate control measures to curtail the spread of the coepidemic disease. Numerical simulations are carried out to confirm the theoretical results.